Particulate organic carbon (POC) fluxes in the Canary Current upwelling region - Arístegui, Javier; Montero, María Fernanda; Hernández-Hernández, Nauzet; Alonso-González, Iván J; Baltar, Federico; Calleja, Maria Ll; Duarte, Carlos Manuel (In: Arístegui, J et al. (2021): Suspended particulate and dissolved organic carbon (POC and DOC), electron transport system (ETS) activity, derived respiration and POC fluxes in the Canary Current upwelling region [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.930838, 2021)
The present data were collected from two cruises that took place in the Canary Current from September 10 to October 1, 2002 (COCA I) and from May 21 to June 7, 2003 (COCA II). The study was conducted along two zonal sections (21ºN and 26ºN) extending from the coastal upwelling to the open ocean at 26ºW, and focused on the epipelagic (0-200 m) and mesopelagic (200-1000 m) zones. The cruises consisted of a total of 31 hydrographic stations and 10 biogeochemical stations, half of them along each section, which were roughly equidistant. At each biogeochemical station free-drifting sediment traps were deployed for 24 h to collect sinking particles at 200 m depth.
Keywords: Canary Current upwelling region; Dissolved Organic Carbon; ETS activity; mesopelagic respiration variability; suspended and sinking particulate organic carbon